AN LC- MS/MS METHOD FOR THE DETERMINATION OF OMEPRAZOLE ON PROTON PUMP INHIBITOR IN HUMAN PLASMA - T. Sudha; Kalan Kumar Reddy; P. V. Hemalatha; V. R. Ravikumar (Indonesian Journal of Pharmacy, 2016)
A sensitive and selective liquid chromatographic method coupled with tandem mass spectroscopy (LC-MS/MS) was developed for the quantification of omeprazole in human plasma. Lansoprazole was used as internal standard with plasma samples, extracted using 10mM ammonium acetate. A centrifuged upper layer was then evaporated and reconstituted with Acetonitrile: mobile phase buffer 70:30%v/v. The reconstructed samples were injected into a C18 column purospher star 5µ. The mobile phase was composed of ACN: mobile phase buffer (5mm ammonium bicarbonate buffer) in the ratio of 70:30%v/v with flow rate 1.0mL/min. The mass spectrometer was operated using positive ion mode and turbo electro spray ionisation. Nitrogen was used as the nebulizer, curtain, collision and auxiliary gases. Using MS/MS with multiple reactions monitoring (MRM) mode, omeprazole was detected without severe interferences from plasma matrix. Detection of omeprazole in human plasma was accurate and precision. This method has been successfully applied to the study of omeprazole in human specimensKeywords: Proton pump inhibitor, omeprazole, lansoprazole, LC-MS/MS, liquid liquid  extraction